Kinerja Keuangan dan Harga Saham: Peran Umur Perusahaan pada Sektor Energi BEI Periode 2021-2024 - Windyaningsih Dwi Astuti; Hasim As’ari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Stock prices are influenced by various internal company factors, including financial performance and company characteristics. This study aims to analyze the effect of profitability, solvency, and liquidity on stock prices in energy sector companies listed on the Indonesia Stock Exchange (IDX), and test the role of company age as a moderating variable. This study uses a quantitative approach with multiple linear regression methods and moderation interaction tests. The sample consists of energy sector companies that are consistently listed on the IDX in the 2021-2024 period. The results show that Return on Equity (ROE) has a positive and significant effect on stock prices, while Debt to Equity Ratio (DER) and Current Ratio (CR) have no significant effect. Company age has a significant effect and moderates the relationship between DER and CR on stock prices. Profitability and company age are important factors in determining stock value. Investors are advised to consider these indicators in making decisions, while management needs to maintain long-term financial performance and reputation. Further research can examine other external variables and industry sectors.